Physicochemical Changes During Processing of Chinese Xuanwei Ham - Aixiang Huang; Sarote Sirisansaneeyakul; Changrong Ge; Zongdao Chen; Qichao Huang; Wen Qin; Yusuf Chisti (Agriculture and Natural Resources, 2011)
Fifty porcine hind legs were processed into dry-cured ham using the traditional Xuanwei process. Sensory and physicochemical changes during processing were studied. The sensory traits (color, texture, odor, taste) of the ham improved during the 4 mth fermentation stage. The moisture content and water activity of muscles decreased and the salt content increased during fermentation. Moisture and water activity of muscles affected the development of a surface crust that is not wanted. Total volatile basic nitrogen, NaNO2 in all muscles and the acid value in the subcutaneous fat increased during processing. The peroxide value increased with time during prefermentation and decreased during fermentation. Use of 90 mg NaNO2 per kilogram of meat improved the color of the final product without posing any food safety issues. During the salting, the pH of the meat decreased with time, but the pH increased rapidly during fermentation. The percentage of saturated free fatty acids increased during fermentation while the percentage of unsaturated free fatty acids decreased. This suggested that the unsaturated free fatty acids were the main fatty acids that underwent peroxidation during the ham fermentation.